2013
DOI: 10.1111/cei.12116
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD45RA−FoxP3high activated regulatory T cells are functionally impaired and related to residual insulin-secreting capacity in patients with type 1 diabetes

Abstract: Summary Accumulating lines of evidence have suggested that regulatory T cells (Tregs) play a central role in T cell+ FoxP3 + T cells was significantly higher in patients with type 1A diabetes with detectable C-peptide but not in patients with type 1A diabetes without it and with fulminant type 1 diabetes. A proliferation suppression assay showed that a-Tregs were functionally impaired both in fulminant type 1 diabetes and in type 1A diabetes. In conclusion, a-Tregs were functionally impaired, related to residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…While the majority of studies have reported no differences in the frequency of T regs in peripheral blood isolated from T1D patients, defects in T reg phenotype and suppressive capacity have been reported (20-24). Unfortunately, the majority of data obtained from T1D patients is from peripheral blood, due to the feasibility of obtaining pancreas samples from T1D patients.…”
Section: Loss Of Treg Phenotype and Function In T1d And Autoimmune DImentioning
confidence: 96%
“…While the majority of studies have reported no differences in the frequency of T regs in peripheral blood isolated from T1D patients, defects in T reg phenotype and suppressive capacity have been reported (20-24). Unfortunately, the majority of data obtained from T1D patients is from peripheral blood, due to the feasibility of obtaining pancreas samples from T1D patients.…”
Section: Loss Of Treg Phenotype and Function In T1d And Autoimmune DImentioning
confidence: 96%
“…Treg cell is another subset of T helper cells and has also been shown to be involved in diabetes. Clinical and animal studies have demonstrated that the diabetic subjects usually had decreased Treg cell activity and low levels of Treg-related cytokines (24). Enhancement of Treg cell activity, either by adoptive transfer or supplementation of supporting cytokines, such as IL-2, is considered as one of the therapeutic methods to diabetes (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis, psoriasis, Type I diabetes and also AChR-MG patients show a significant decrease in the suppressive function of Tregs compared with HC [10,[67][68][69]. This section focuses on discussing the several studies that have been undertaken on characteristic, quantitative and qualitative changes of Tregs in MG patients.…”
Section: Studies Of Tregs In Patients With Mgmentioning
confidence: 99%